Ionic Polymer Metal Composites for Sensors and Actuators - Inamuddin; Asiri, Abdullah M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the fundamental of bending actuation with a focus on ionic metal composites. It describes the applications of ionic polymer metal composite (IPMC) actuators, from conventional robotic systems to compliant micro robotic systems used to handle the miniature and fragile components during robotic micro assembly. It also presents mathematical modelings of actuators for engineering, biomedical, medical and environmental systems. The fundamental relation of IPMC actuators to the biomimetic systems are also included.
Fundamental of ionic polymer metal composite actuators -- Back relaxation in ionic polymer metal composite actuators -- Characterization of ionic polymer metal composite actuators -- Ion transport in ionic polymer metal composite actuators -- Ionic polymer metal composite actuators operable in dry conditions -- Biomimetic systems based on ionic polymer metal composite actuators -- Ionic polymer metal composite membranes: Methods of preparation -- Modelling of hysteresis in IPMC actuators -- Study on time dependent bending response of IPMC actuator -- Methods of position control of an IPMC actuator used in micro assemblies -- Role of metal ion implantation on ionic polymer metal composite membranes -- Nafion: The inception to current trends as IPMC actuator -- Metal-organic framework composites IPMC actuator -- Sulfonated polyetherimide based ionic polymer metal composite actuators -- Chitosan-based ionic polymer metal composite actuators -- Poly(ether ether ketone) based ionic polymer metal composite actuators -- Sulfonated polysulfone based ionic polymer metal composite actuators -- Conducting polymer based ionic polymer metal composite actuators -- Pneumatic IPMC bending actuator -- Compliant micro robotic systems to handle the miniature and fragile components -- Diaphragm based on IPMC actuator for micropump devices -- Humidity sensor based on IPMC actuator -- Displacement sensors based on IPMC actuator -- Pressure sensors based on IPMC actuator -- Stress sensors based on IPMC actuator -- Palpatory pulse-rate extraction based on IPMC actuator -- Micromanipulation of ionic polymer metal composite based microgripper -- Robotic assemblies based on IPMC actuators.
Keywords: Ceramic materials; Optical materials; Polymers; Mechanical engineering; Biomedical engineering; Ceramics; Optical Materials; Polymers; Mechanical Engineering; Biomedical Engineering and Bioengineering